Capacity Building of Entrepreneurial Human Resources Based on Green Skills to Support Sustainable Development in the MSME Sector - Fatmawati, Irma; Surya, Elfitra Desy; Indrawan, Muhammad Isa (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of competencies, education and training, work experience, and individual performance on sustainable development with green skills as a mediating variable. A quantitative approach is used with the SEM-PLS method to process data from relevant respondents. The results of the analysis show that all independent variables have a significant effect on green skills and sustainable development directly. In addition, green skills have been shown to mediate the relationship between these variables to sustainable development. These findings are in line with the theory of human capital and the resource-based view, which emphasizes the importance of human resource development in achieving sustainable long-term goals. This research reinforces previous studies that highlight the role of training, competence, and work experience in improving green skills and supporting sustainable development. This study has limitations in the scope of the area and type of industry surveyed, and has not taken into account external environmental factors such as government policies. Further research is suggested to expand the sample and add external variables as controls. Organization should invest in employee competencies, education, and training to enhance green skills, which in turn support sustainable development.